2013
DOI: 10.3390/su5104461
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Implications of Urban Sprawl in the Helsinki Metropolitan Area

Abstract: Suburban households living in spacious detached houses and owing multiple cars are often seen as main culprits for negative greenhouse consequences of urban sprawl. Consequently, the effects of sprawl have been mostly studied from the viewpoints of emissions from home energy consumption and private driving. Little attention has been paid to the changes in other consumption. In this paper, urban sprawl is linked to the proliferation of semi-detached and detached housing, described as a low-rise lifestyle, at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…For example, even when controlling for income, city center residents may cause higher indirect emissions through elevated consumption of goods and particularly services (Ala-Mantila et al 2014). Studies on consumption-based carbon footprints and energy requirements in the built environment have found that the total environmental pressure per capita is strikingly similar regardless of the residential location when income is controlled (Lenzen et al 2004, Ornetzeder et al 2008, Heinonen et al 2013b, Minx et al 2013, Wiedenhofer et al 2013, Ala-Mantila et al 2013, Ottelin et al 2015, Chen et al 2017, although the emissions caused by car use increase strongly with increasing distance to city center and decreasing urban density. Ottelin et al (2017) suggest that this is partly due to the rebound effect for reduced car-ownership and driving.…”
Section: Rebound Effect 421 Consumption-based Environmental Assessmentioning
confidence: 99%
“…For example, even when controlling for income, city center residents may cause higher indirect emissions through elevated consumption of goods and particularly services (Ala-Mantila et al 2014). Studies on consumption-based carbon footprints and energy requirements in the built environment have found that the total environmental pressure per capita is strikingly similar regardless of the residential location when income is controlled (Lenzen et al 2004, Ornetzeder et al 2008, Heinonen et al 2013b, Minx et al 2013, Wiedenhofer et al 2013, Ala-Mantila et al 2013, Ottelin et al 2015, Chen et al 2017, although the emissions caused by car use increase strongly with increasing distance to city center and decreasing urban density. Ottelin et al (2017) suggest that this is partly due to the rebound effect for reduced car-ownership and driving.…”
Section: Rebound Effect 421 Consumption-based Environmental Assessmentioning
confidence: 99%
“…The decomposition of "origin" and "destination" of embodied emissions by sector in the carbon map is just an additional step introduced by but consumption-based emissions (or CFs) of cities have been calculated with (multi-region) input-output analysis before [42][43][44][45][46]. The MRIO table for this study was derived from the Australian Industrial Ecology Virtual Laboratory [47] (see the heat map in the Figure S1), which can distinguish regions with a population of 10,000 residents (denoted SA2 region) [48].…”
Section: Methodology and Datamentioning
confidence: 99%
“…The five most influential environmental issues raised in a project design process are: urban sprawl (17%), buildings' energy consumption (16%), mobility and transportation (14%), urban microclimates (11%), and natural resource management (10%). Apart from the last item, these energy-related issues can all be linked to climate mitigation actions because they directly or indirectly impact GHG emissions [47][48][49][50].…”
Section: City and Building Designers And Climate Change: What Do Theymentioning
confidence: 99%